First high-resolution marinopalynological stratigraphy of Late Quaternary sediments from the central part of the Bulgarian Black Sea area - Filipova-Marinova, Mariana; Pavlov, Danail; Coolen, Marco; Giosan, Liviu (Advancing Pleistocene and Holocene climate change research in the Carpathian-Balkan region, 2013)
Spores, pollen and dinoflagellate cysts of Late Pleistocene and Holocene sediments were analyzed from Giant Gravity Core 18 from the Black Sea continental slope, recovered from a water depth of 971 m. The investigated length of the core is 203.5 cm. It includes 3 lithological units: light grey clay, sapropels and coccolith-bearing ooze. The core was sampled at 5–10 cm intervals. Sampling of the interval 141.5–126 cm was carried out at every cm. AMS radiocarbon dating of bulk organic carbon was performed on 18 selected sediment layers. This chronological data allowed the first high-resolution pollen stratigraphy of Late Quaternary sediments from the western Black Sea area to be presented. The percentage spore–pollen diagram is divided into 6 local pollen assemblage zones. The trends in the vegetation dynamics and climate changes and the early history of migration of the majority of the arboreal taxa that nowadays occur in the Eastern Balkan Range were traced out. The palynological record suggests that open oak forests were spread in the Eastern Balkan Range at the beginning of the Holocene and shows early migration of the major temperate arboreal species such as Quercus, Ulmus, Tilia and Carpinus betulus. This vegetation palaeosuccession continues with the spreading of mixed oak forests from 8950 until 2620 cal. BP (8650 ± 40 until 3120 ± 35 14C BP) followed by destructive changes due to human impact and climate deterioration. A cooling of Holocene climate that is well known in the North Atlantic region as the “8200 yrs cold event” is identified for the first time in marine records from the Bulgarian Black Sea area. The assemblages of dinoflagellate cysts and acritarchs were investigated to provide a reconstruction of surface seawater salinity and surface seawater temperature changes. Two main dinoflagellate cyst assemblages, one dominated by fresh- to brackish water species such as Spiniferites cruciformis and Pyxidinopsis psilata and a subsequent one, that is characterized by euryhaline marine Mediterranean species such as Lingulodinium machaerophorum, Spiniferites belerius, Spiniferites bentorii, Operculodinium centrocarpum and acritarchs Cymatiosphaera globulosa testified a change in SSS from low salinity (
id: 2330